VR Cognitive-based Intervention for Enhancing Cognitive Functions and Well-being in Older Adults with Mild Cognitive Impairment: Behavioral and EEG Evidence - Pattrawadee Makmee; Peera Wongupparaj (Psychosocial Intervention)

(untitled)
Objective: Mild cognitive impairment (MCI) has been recognized as a window of opportunity for therapeutic and preventive measures to slow cognitive decline. The current study investigated the efficacy of the virtual reality (VR) cognitive-based intervention on verbal and visuospatial short-term memory (STM), executive functions (EFs), and wellbeing among older adults with and without MCI. Method: The immersive VR cognitive-based intervention comprised eight 60-minute sessions, held twice a week over a span of 30 days. The participants consisted of 31 non-MCI older adults in the experimental group (mean age ± SD = 66.31 ± 3.12 years), 29 older adults with MCI in the experimental group (mean age ± SD = 68.19 ± 5.03 years), and 30 non-MCI older adults in the control group (mean age ± SD = 64.97 ± 3.35 years). The dependent variables were assessed by using a battery of computerized test, the well-being of older people questionnaire and resting-state EEG. A repeated-measures ANCOVA was employed to examine the effects of the developed VR intervention. Results: Significant improvements were observed in both STMs and EFs following the intervention, as indicated by behavioral and EEG findings, ranging from small to large effect sizes (i.e., = .05-.17). However, enhanced wellbeing was specifically observed among older adults with MCI in the experimental group, F(2, 87) = 6.78, p .01, = .11. Conclusions: The present findings lend support to the efficacy of VR cognitive-based interventions across clinical and non-clinical populations. These results underscore the immediate impact of the intervention across multimodal assessments, including neurophysiological changes, cognitive, and behavioral outcomes.